Pengaruh Emotional Intelligence terhadap Job Satisfaction yang dimediasi oleh Work Engagement pada Dokter Gigi di RSGMP FKG Usakti - Nadhia Sari Afiana; Andreas Wahyu Gunawan P (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to determine the effect of Emotional Intelligence on Job Satisfaction mediated by Work Engagement on dentists at RSGMP FKG Usakti. Data analysis using SEM with smartPLS software. All instruments are tested for validity and realibiity first. Data were collectedby distributing questionnaires which were measured using interval scale, which is likert scale, 200 respondents were found who had filled out the questionnaire. Result of this study shows that Emotional Intelligence has an effect on Job Satisfaction, Work Engagement has an effect on Job Satisfaction and Emotional Intelligence has an effect on Job Satisfaction mediated by Work Engagement. This study is expected to be a reference for further research. The HR Managerial of RSGMP-FKG Usakti needs to pay attention and increase the level of Emotional Intelligence through training or training, providing periodic refreshments and motivation so that dentists have the enthusiasm to start activities. And it is also expected to pay attention to the rewards and salaries of the dentists at the RSGMP FKG Trisakti University in order to create a better performance and work environment.